The effect of contralateral carotid occlusion in patients undergoing carotid artery endarterectomy - Duarte-Gamas,Luís (2022)
Abstract Introduction: Contralateral carotid occlusion (CCO) is considered a high-risk condition for patients undergoing carotid artery endarterectomy (CEA). Patients with a CCO may be intolerant to carotid cross-clamping during CEA, thus prone to postoperative adverse neurological outcomes. Patients with CCO may also have a higher burden of atherosclerotic disease, leading to a higher rate of cardiovascular events. Methods: A Medline search was performed in order to identify publications focused on the impact of CCO on outcomes after CEA. Results: Patients with CCO present a higher incidence of intolerance to carotid cross-clamping. The rates of shunt use are higher in patients with CCO. In the postoperative period, patients with CCO show a higher rate of stroke. Evidence regarding the effect of CCO on long-term outcomes remains controversial, with most studies reporting a lack of association between CCO and adverse long-term outcomes after CEA. Conclusion: Patients with CCO have an increased risk of postoperative adverse outcomes. The best strategy for this group of patients should be based on a case-by-case approach.